2024
DOI: 10.3892/mmr.2024.13162
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological activity of capsaicin: Mechanisms and controversies (Review)

Wei Zhang,
Yu Zhang,
Jinke Fan
et al.

Abstract: Capsaicin, which is abundant in chili peppers, exerts antioxidative, antitumor, antiulcer and analgesic effects and it has demonstrated potential as a treatment for cardiovascular, gastrointestinal, oncological and dermatological conditions. Unique among natural irritants, capsaicin initially excites neurons but then ‘calms’ them into long-lasting non-responsiveness. Capsaicin can also promote weight loss, making it potentially useful for treating obesity. Several mechanisms have been proposed to explain the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…Capsaicin, a primary component of chili peppers and a highly pungent alkaloid of vanillin [65], is also known to be a TRPV1 agonist that has various pharmacological effects, including analgesic [66], antiobesity [67], anti-inflammatory [68], antioxidant [69]…”
Section: The Trpv1 Agonist Capsaicin Inhibits Tnbcmentioning
confidence: 99%
“…Capsaicin, a primary component of chili peppers and a highly pungent alkaloid of vanillin [65], is also known to be a TRPV1 agonist that has various pharmacological effects, including analgesic [66], antiobesity [67], anti-inflammatory [68], antioxidant [69]…”
Section: The Trpv1 Agonist Capsaicin Inhibits Tnbcmentioning
confidence: 99%
“…Actually, it is an imported ingredient because it was introduced in Europe only after the discovery of the Americas, but in Calabria, it is so diffused that it can mostly be considered a determinant for many recipes and for Morzeddhu too. The main component responsible for the spicy effect is capsaicin [ 51 ]. Its presence in the dish is mandatory but can be quantitatively different on the basis of the preferences of the cooker and the type of peperoncino used.…”
Section: Nutritional Facts and Bioactive Compounds Of Traditional ...mentioning
confidence: 99%
“…It has been observed that these vesicular aggregates improve skin permeation and lidocaine drug deposition on the skin and can act as a capsaicin transporter. Capsaicin (CA) is another analgesic, antioxidant, and antitumoral drug [ 7 ]. This compound acts on skin nociceptors involved in pain signals.…”
Section: Introductionmentioning
confidence: 99%